EFEKTIFITAS PENGGUNAAN CANGKANG KERANG DARAH (Anadara granosa) SEBAGAI FILTER AIR TANAH DI KOTA TARAKAN - Rattu, Claudia Constancy; Achyani, Ratno; Rachmawani, Dori (Jurnal Borneo Saintek, 2022)
Tarakan City has the potential of groundwater for the need for clean water. However, it must be treated first so that its quality meets the standard required among the efforts of filtration by utilizing the waste of Abalone shells (Anadara sp). The purpose of the research was to determine the effectiveness of using Abalone shells (Anadara sp) as a groundwater filter in Tarakan city. The research method used a complete randomized design (RAL) method. The material used Dara Shell (Anadara sp) filter levels of 30cm, 60cm, and 100 cm combined with active charcoal, quartz sand and gravel to determine the best composition. The parameters were tested based on Minister of Health Regulation No. 32 of 2017 (Standard Water Quality for Hygiene Sanitation Requirement): turbidity, colour, pH, temperature, TSS, TDS, nitrate, nitrite, Fe heavy metal and Mn. Research results showed that the filter’s effectively increased pH values by 54% and decreased the concentration of consecutive Mn heavy metals 83%. Level 60 cm filters effectively decrease nitrite, TDS, cloudy and colouration levels by 31%, 44%, 26% and 54%, respectively. While the 30 cm filter level effectively lowers the TSS level by 75%.